Marketing car love in an age of fear: an anthropological approach to the emotional life of a world of automobiles - Lutz,Catherine (2015)
The emotional life of car drivers and passengers in the United States is complex, with car marketing and a wider car system of infrastructure, regulation, risk, and profit shaping those affects. Based on anthropological research with drivers, buyers, marketers, and emergency personnel, this paper outlines a political economy of automobile affect in the United States. It focuses on the emotional encapsulation and individualism that car culture encourages, the remaking of the car interior as a highly emotional marketing and political space, and the fear of crime and crashes that car marketing both elides and banks on.